Social gradient in health-related quality of life among urban residents in Limassol, Cyprus - Ellina, Panayiota; Kouta, Christiana; Lambrinou, Ekaterini; Nicolaou, Christiana; Middleton, Nicos (My University, 2018)
Background: Unlike several European countries, there is lack of data on the extent and magnitude of social inequalities in health in Cyprus. Methods: A door-to-door survey of residents aged 45-64 (N = 450, 50:50 gender quota) across 45 randomly selected neighbourhoods from different city quarters, stratified by population density and proportion of adult residents with tertiary education. The SF-36 was used to measure the health-related quality of life (HRQoL) and differences in terms of educational attainment, income and occupational classification were explored.
Keywords: Social inequalities; Health; Cyprus